Implementasi Independensi dan Pengalaman Kerja terhadap Kualitas Audit di Inspektorat Kota Tasikmalaya Tahun 2019 - Budi Harto; Sinta Juwitasari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
This study aims to examine and determine the effect of independence and work experience on audit quality in the Inspectorate of Tasikmalaya City. This research is a quantitative research with a descriptive approach. The population in this study was the Auditor of the City of Tasikmalaya, totaling 18 people. The data used in this study are primary data collected through a questionnaire survey directly. Data analysis uses multiple linear regression analysis. Multiple linear analysis. The results of the study with multiple linear regression analysis showed that independence and work experience had a positive and significant effect on audit quality. There is a positive and significant effect of Independence and Work Experience on Audit Quality simultaneously in the Tasikmalaya City Inspectorate. This is indicated by the calculated F value of 122.701 is greater than the F table of and the probability value of the significance of Independence and Work Experience is 0.000 and smaller than 0.05. The coefficient of determination shows the value of R2 (R Square) is quite high at 0.942, this shows that 94.2% of audit quality in the Tasikmalaya City Inspectorate is influenced by Independence and Work Experience while the remaining 5.8% is influenced by other variables outside this study.